LET'S SET THE RECORD STRAIGHT... DO WE REALLY NEED LAWS TO REGULATE SMOKING IN PUBLIC? ARE PUBLIC SMOKING LAWS ENFORCE ABLE? WORKPLACE SMOKING LAWS WON'T WORK (Tufts Archival Research Center, 2007)
Tobacco Institute advertisements against legislation restricting smoking. Argues that proposals to segregate smokers from non smokers are a matter for private solution. Supports this argument with statements from California and Florida citizens. Predicts enforcement of such laws would be impossible, as it would be an administrator's nightmare and the police "have better things to do." Questions whether minorities in particular will be targeted. Accuses workplace smoking restrictions of being impractical. Suggests that the "prohibitionists" will not stop at smoking restrictions.